2015
DOI: 10.1111/ans.12972
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the ureter

Abstract: A 57-year-old woman was referred following an acute episode of left-sided pyelonephritis associated with Klebsiella spp infection. After antibiotic treatment and resolution of the infection, the left flank pain continued and imaging revealed left hydronephrosis and hydroureter, with apparent obstruction on the left pelvic sidewall associated with the presence of a round lesion approximately 36 mm in diameter (Fig. 1). The left ovary appeared to be in close relation to the obstructing lesion, but separate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As with their lower tract counterparts, all previously reported cases of ureteral leiomyoma were treated surgically with either segmental ureterectomy or nephroureterectomy. 9,10 Unlike the bladder, complete endoscopic management of tumors in the ureter is limited given the smaller working channel of the ureter and the relatively thin muscle layer, the latter of which increases risk for perforation. These challenges likely account for the absence of endoscopic approaches to ureteral leiomyoma in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…As with their lower tract counterparts, all previously reported cases of ureteral leiomyoma were treated surgically with either segmental ureterectomy or nephroureterectomy. 9,10 Unlike the bladder, complete endoscopic management of tumors in the ureter is limited given the smaller working channel of the ureter and the relatively thin muscle layer, the latter of which increases risk for perforation. These challenges likely account for the absence of endoscopic approaches to ureteral leiomyoma in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to our research, only 14 cases have been reported since the first report published by Leighton et al . in 1955 [ 2 15 ], making the present patient the 15th (Table 1 ). Apart from one patient being an infant, most of the patients were aged between 30 and 60 years (average age 41 years), including the present case, aged 51 years.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] 32 F Lt 112 × 70 × 15 Upper/middle Nephroureterectomy Englund et al . [ 15 ] 57 F Lt 36 Lower Tumor resection Present case 51 M Rt 20 × 10 Upper Nephroureterectomy UPJ: Ureteropelvic junction …”
Section: Discussionmentioning
confidence: 99%
“…Ureteral leiomyomas are very rare benign neoplasms that usually present with symptoms of ureteral obstruction [3]. Since first described in 1955 [4], only 13 cases of leiomyoma of the ureter have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Since first described in 1955 [4], only 13 cases of leiomyoma of the ureter have been reported to date. Advances in ureteroscopy have enabled more conservative treatments of these tumors, allowing preservation of the kidney [3]. This report describes a patient with a renal pelvis leiomyoma who underwent kidney-sparing surgery using a percutaneous approach.…”
Section: Introductionmentioning
confidence: 99%